2012
DOI: 10.1007/s10753-012-9486-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of PPARγ in COX-2 Activation in Mycobacterial Pulmonary Inflammation

Abstract: Preliminary studies show that intranasal (i.n.) administration of BCG in mice induces M1 activation of alveolar macrophages (MØ) that increase TNF-α production and cyclooxygenase-2 (COX-2) expression but reduce constitutive peroxisome proliferator-activated receptor gamma (PPARγ) expression. However, COX-2 is catalytically inactive for prostaglandin E2 release, unlike COX-2 active in M1 activation in vitro by BCG. In this study, we determined the role of PPARγ for BCG-induced M1 activation in vivo and in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…These included (i) mice deficient in methionine sulfoxide reductase A, an enzyme protecting hosts from oxidation, (ii) mice deficient in Flt-1 tyrosine kinase, an enzyme regulating monocyte infiltration, (iii) mice deficient in CRTH2 (chemoattractant receptor-homologous molecule expressed on Th2 cells), a receptor of PGD 2 derived from activated mast cells, and (iv) mice that were treated with GW9662, a PPAR␥ antagonist. Our published (14) and unpublished (data not shown) results, however, showed that alveolar M in these animals still exhibited NE-dissociated COX-2 when activated by i.n. BCG and NE-associated COX-2 when activated in vitro.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…These included (i) mice deficient in methionine sulfoxide reductase A, an enzyme protecting hosts from oxidation, (ii) mice deficient in Flt-1 tyrosine kinase, an enzyme regulating monocyte infiltration, (iii) mice deficient in CRTH2 (chemoattractant receptor-homologous molecule expressed on Th2 cells), a receptor of PGD 2 derived from activated mast cells, and (iv) mice that were treated with GW9662, a PPAR␥ antagonist. Our published (14) and unpublished (data not shown) results, however, showed that alveolar M in these animals still exhibited NE-dissociated COX-2 when activated by i.n. BCG and NE-associated COX-2 when activated in vitro.…”
Section: Discussionmentioning
confidence: 54%
“…PPAR␥, consisting of the 53-kDa PPAR␥1 subunit and the 57-kDa PPAR␥2 subunit, is constitutively expressed by alveolar M but not alveolar epithelial cells; our previous study (14) indicated that the major PPAR␥ bands were undetectable in the BCGtreated cells. While clearly visualized in the BCG/CT-treated cells, levels were still less than 15% of those seen in the cells treated with CT alone (Fig.…”
Section: Coadministration Of Bcg and Ct Induces Active Cox-2 In Alveomentioning
confidence: 83%
See 2 more Smart Citations
“…For example, pathogen elimination is facilitated by PPARg-polarized macrophages via enhanced phagocytosis and release of NO, reactive oxygen species, cytotoxic cytokines and altered glucose metabolism (e.g. against Pseudomonas, 36 Mycobacterium, 37 Trypanosoma, 38 Leishmania, 39 Plasmodium 40 and Candida 41 ) in mice and in patients with chronic granulomatous disease (CGD). 42 Nonself recognition of tumors as an "internal pathogen" may be exploited by the same mechanism.…”
Section: Discussionmentioning
confidence: 99%